FTO-mediated MMP1 m6A modification promotes osteogenic differentiation of bone marrow mesenchymal stem cells via the ERK pathway in congenital scoliosis - Jie Dai; Gang Xiang; Jiong Li; Gengming Zhang; Guanteng Yang; Lige Xiao; Yunjia Wang; Hongqi Zhang (Scientific Reports)
Abstract Bone formation, metabolism, and the stability of the bone marrow microenvironment are all impacted by the imbalance in the differentiation potential of bone marrow mesenchymal stem cells (BMSCs). Despite this, it is unknown how BMSCs affect congenital scoliosis (CS). As a result, our research now focuses on explaining its associated impact and mechanism. In eukaryotic cells, N6-methyladenosine (m6A) is the most prevalent post-transcriptional alteration. The role of fat mass and obesity-related genes (FTO), an m6A demethylase, in regulating the differentiation of BMSCs is still unknown. We assessed alterations in the mRNA and protein levels of genes linked to the differentiation of BMSCs using samples taken from CS. According to our findings, According to our findings, FTO inhibits osteogenic differentiation and promotes the adipogenic differentiation of BMSCs. MMP1 knockdown has an inhibitory effect on BMSC osteogenic differentiation, whereas MMP1 overexpression promotes it. A specific ERG inhibitor called PD98059 prevents MMP1-mediated promotion. Additionally, our research revealed that FTO affects how BMSCs can differentiate in CS patients by regulating MMP1 levels. FTO-mediated MMP1 m6A modification underlies MMP1’s promotion of osteogenic differentiation via the ERK pathway, implying that it could be a viable treatment target for CS.